Touching the void: The loss of containment and the space between operational and entrepreneurial leadership in the K2 disaster - Cantarelli, Chantal C.; Davis, Kate; Kutsch, Elmar; Turner, Neil; Denyer, David; Turnbull James, Kim (European Academy of Management (EURAM), 2024)
In this paper, we seek to understand how members of a collective facing a novel, unprecedented challenge can lose an integrated and realistic connection to the people, events, opportunities, and threats around them. Using extensive data, including interviews with survivors and unique video footage we analyze how eleven experienced climbers lost their lives in 2008 attempting to summit K2, the world’s second-highest mountain. Existing theories of leadership and information-processing views of human cognition do not fully explain observations from our qualitative study. However, containment and social defense constructs suggest how and why people failed to respond to the impending disaster. We offer four key findings. First, destabilizing conditions can erode operational leadership resulting in a breakdown of the traditional sanctuaries of procedure, role clarity, hierarchy, and positional authority. Second, despite clear, escalating threats and the potential for impending disaster, individual and collective responsiveness, proactivity, and adaption can fail to materialize. Third, people’s responses to novel, unprecedented circumstances are deeply connected to and reliant on the ways collectives develop to contain anxiety. Finally, loss of containment can result in a void, disabling people from confronting and adapting to challenging situations realistically and competently.
Keywords: complexity leadership; extreme context; containment of anxiety; social defenses